Deacon Locke went to prom - Katcher, Brian 1975- (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2017)
Promposals are taking over Deacon Locke's high school and there is no place left to hide. But even with graduation looming, shy and unusually tall Deacon doesn't think he can get up the nerve to ask anyone to the dance. Especially given all the theatrics. It isn't until Deacon confides in his witty and outgoing best friend Jean that he realizes she could be a great person to take. Only problem is Jean isn't your typical prom date. She's older. A lot older. And she's Deacon's grandmother. But when Deacon meets Soraya -- a girl unlike any other he's ever met -- he fears he has totally squandered his chances of having a prom he'll never forget. Deacon couldn't be more wrong. About everything